Conceptual models of greenspace and health - Mansor, Mazlina; Ghani, Norfaezah; Harun, Nor Zalina; Zakariya, Khalilah (American Scientific Publishers, 2017)
The relationship between greenspace and health is important to be explored because it relates to health issues, which are prevalent among city citizens. Urban greenspace can improve residents' lifestyle for healthier living. The paper presents a review of evidence that links greenspace and health through various conceptual models. The literature was drawn from research articles published between 2007 and 2012. The findings identified parameters, which include factors that influence the use of open spaces, physical activity and effects of activity on health. Seventeen conceptual models were derived from the review, among others; a socio-ecological framework and nature-based health promotion model. The themes emerged from the conceptual models are: individual factors (e.g. gender differences, social conditions, demographic, socioeconomic factors), physical and environmental factors (e.g. accessibility, walkability, environmental stresses and resources, type of setting, greenspace, biodiversity, city planning and policy, and greenspace planning), health effects (e.g. neighborhood satisfaction, social health, mental health, health status, mental restoration), and the use of open space (e.g. physical activity, behavior, social interaction). It shows that research that links greenspace with health has expanded over the years and has continuously been a topic of interest since the 1970s. Keywords: Greenspace, Health, Review, Conceptual frameworks, Models